Dual left anterior descending artery with anomalous left anterior descending artery from pulmonary artery: double trouble. (19th December 2022) - Kakarla, Saikiran; Sasikumar, Deepa; Valakkada, Jineesh
Abstract: Anomalous origin of left anterior descending artery (LAD) from pulmonary artery (ALADCAPA) with dual LAD from left sinus is an extremely rare coronary anomaly. The diagnostic challenge lies in differentiating this from a coronary cameral fistula. Surgical reimplantation of the anomalous LAD is recommended to prevent the risk of myocardial ischaemia and ventricular arrhythmias. Abstract : A 5-year-old girl who had elective PDA coil closure at 2 years of age came for follow-up visit.